Development of sulfide, nitrogen co-doping hollow carbon with wideband electromagnetic absorption capability. Issue 38 (12th June 2020) - Bao, Wenli; Chen, Cong; Si, Zhenjun
Abstract : Exploration of an economic, easy-producing method to develop high-performance electromagnetic absorber has been a global research interest, owing to the increasingly electromagnetic pollution and interference. Abstract : Exploration of an economic, easy-producing method to develop high-performance electromagnetic absorber has been a global research interest, owing to the increasingly electromagnetic pollution and interference. In this work, sulfide, nitrogen co-doping carbon (NS–HCS) has been successfully prepared by an in situ copolymer and subsequent calcination reaction. The morphologies and phase compositions of these as-prepared samples are analyzed via the transmission electron microscopy (TEM), element mappings, X-ray diffraction (XRD) and X-ray photoelectron spectrum (XPS). The result confirms the hollow shaped structure of amorphous carbon is constructed with various types of N, S based covalent bonds. The dotted N and S elements are contribution for the conductive loss and dipole polarization relaxation behavior. The minimum reflection loss value of −34 dB, and effective bandwidth reaches 6.8 GHz with only 1.6 mm. The as-prepared wideband electromagnetic absorber will pave a simple and effective method to obtain lightweight, broadband and thin thickness electromagnetic absorption materials.